A congruence analysis of the inequality–conflict nexus: Evidence from 16 cases. (July 2019) - Bartusevičius, Henrikas
The relationship between inequality and civil conflict has attracted considerable interest in conflict research. Recent large -N studies have shown that inequalities significantly contribute to the outbreak of civil conflict and have proposed a number of causal pathways to account for this. These pathways, however, have rarely been assessed in systematic case-based research. This study implements a "middle -N " qualitative congruence analysis of 16 conflicts, focusing on the observable implications of the pathways through which inequalities are typically theorized to influence conflict. The study finds evidence to support some of the main pathways proposed in the quantitative literature. Furthermore, the analysis finds that different types of inequalities relate to different conflict categories. Specifically, vertical inequalities relate to non-ethnic governmental conflicts (via an "individual deprivation pathway"), regional inequalities to non-ethnic territorial conflicts (via a "separatist pathway"), and horizontal inequalities to ethnic conflicts (via a "group deprivation pathway").